2020
DOI: 10.1302/2058-5241.5.200006
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder biomechanics in normal and selected pathological conditions

Abstract: The stability of the glenohumeral joint depends on soft tissue stabilizers, bone morphology and dynamic stabilizers such as the rotator cuff and long head of the biceps tendon. Shoulder stabilization techniques include anatomic procedures such as repair of the labrum or restoration of bone loss, but also non-anatomic options such as remplissage or tendon transfers. Rotator cuff repair should restore the cuff anatomy, reattach the rotator cable and respect the coracoacromial arch whenever possible. Tendon trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 132 publications
1
37
0
Order By: Relevance
“…The ROM [ 12 , 19 , 44 , 58 , 63 , 70 , 73 , 80 , 82 , 88 , 94 , 95 , 100 , 129 , 132 , 142 , 203 , 206 , 223 , 225 , 232 ] was the third most considered topic. Regarding this, the great amplitude of the shoulder stands out [ 1 ]. This enables the performance of the necessary supracranial motions in the usual range of ADL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROM [ 12 , 19 , 44 , 58 , 63 , 70 , 73 , 80 , 82 , 88 , 94 , 95 , 100 , 129 , 132 , 142 , 203 , 206 , 223 , 225 , 232 ] was the third most considered topic. Regarding this, the great amplitude of the shoulder stands out [ 1 ]. This enables the performance of the necessary supracranial motions in the usual range of ADL.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulders are essential to human beings’ functionality. Their specific biomechanics make shoulders the most mobile joint complex in the body, providing upper limbs with mobility in the three axes of space [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rotator cable was known as the suspension bridge in shoulder force transmission that plays a vital role in force transmission and joint stability [1][2][3]. Research found that rotator cuff tears involving the anterior rotator cable were easily combined with signi cantly large tear patterns and more advanced muscle atrophy as well as higher retear rates after repair [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The rotator cuff cable and rotator cuff interval are among the most recent topics of interest in current literature on shoulders [1,[14][15][16][17]. Most of the research has been published in the last two decades and our understanding of the importance regarding these anatomical structures has improved with biomechanical studies, which has changed the pre-and intra-operative approaches to shoulder surgery [5,14,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation